Preparation and decolorization of sapindus mukurossi extract and its application in sebum-control shampoos - Kaibo Wan; Ling Ma; Diansong Chen; Zhizhen Li; Christos C. Zouboulis; Kuan Chang; Jing Wang (Journal of Dermatologic Science and Cosmetic Technology)
Background: Sapindus mukurossi extract (SME) is a kind of natural surface active ingredient with potential applications in cleansing products. However, the polyphenols and pigments contained in the extract may cause color browning of the products during storage especially at elevated temperatures, affecting its high level addition in the products. Objective: To explore a decolorization process suitable for industrialization realize the high level addition of SME and explore the potential of SME in the field of controlling sebum esters. Materials and Methods: SME was prepared by adsorbing polyphenols on the D301 resin and oxidation decoloring oxidation. Investigated its sebum-control efficacy by SZ95 model and clinical study. Results: The results demonstrate that the D301 resin displays the best adsorption selectivity for polyphenols in SME, and the polyphenol adsorption ratio of D301 resin (5 wt%) can reach 83.6%; The optimal decolorization conditions are pH= 7.8, temperature 73 ℃ and decolorization time 5.7 h when H2O2 content is 6%, The prepared SME shows no obvious changes in color and retain stable during the high temperature (50 °C) test period of 28 days. 4 μg/mL of SME decreases the lipid synthesis of SZ95 cells by 24.8%. The clinic efficacy of the shampoo containing 10% SME (by dry extract weigh) is further evaluated. No significant changes in the skin moisture content and transepidermal water loss (TEWL) are observed within four weeks after using the product, while the scalp sebum level is significantly reduced. Conclusion: In this study, we prepared a light-colored, highly stable SME, enabled its high-level addition in cleansing and care products and found its sebum-control efficacy.